Site-specific seismic hazard and risk potential of Bengal Basin with emphasis on holistic seismic hazard microzonation and its structural impact assessment in the cities of Dhanbad and Mymensingh - Nath, Sankar Kumar; Biswas, Arpita; Srivastava, Anand; Sengupta, Arnab; Ghatak, Chitralekha; Madan, Jyothula (Frontiers in Earth Science, 2022)
The Bengal Basin located in the eastern part of the Indian subcontinent at the conjunction of the Eurasian, Indian and Indo-Burma plates with two progressing deformation fronts viz. the Himalaya and the Indo-Burmese orogenic belts is one of the largest fluvio-deltaic to shallow marine sedimentary basin covered by alluvial plains of Holocene deposits extending from the Himalaya to the Bay of Bengal over thick younger alluvium comprising of shallow layers of silt, clay and sand that can have disastrous consequences due to site-specific ground motion amplification and liquefaction effects. The Basin surrounded by Shillong and Assam Plateau in the northeast is in the active tectonofabric of major active faults and lineaments triggering many devastating earthquakes in the past implicating MM Intensity of VIII-XI in near-source region causing widespread damage and destruction in the Basin thus bringing in the essence of assessing surface level seismic hazard and the risk imposed on the Basin. Consideration of seismicity patterns, fault networks and similarity in focal mechanisms yielded 49 areal seismogenic sources and additional active tectonic features in the 0-25km, 25-70km and 70-180km hypocentral depth ranges, which along with 14 ground motion prediction equations that include site-specific next generation spectral attenuation models pertaining to Northeast India, East-Central Himalaya and Bengal Basin tectonic provinces yielded Probabilistic Peak Ground Acceleration (PGA) at engineering bedrock in the range of 0.08-0.58g. Both the Geophysical and Geotechnical investigations at 6000 sites provided effective shear wave velocity distribution in the range of 113-948m/s on GIS thus classifying the Basin into eleven site classes with ‘None’ to ‘Severe’ liquefaction hazard potential. Systematic nonlinear/ equivalent linear site response analysis and its spectral convolution with firm rock PGA yielded surface-consistent hazard in the range of 0.09-1.17g thus opening up the issue of risk assessment and holistic seismic hazard microzonation of all the cities in the Basin and their structural impact assessment using SELENA-based Capacity Spectrum Method on FEMA and BMTPC-regulated eleven model building types in the damage states of ‘none’, ‘slight’, ‘moderate’, ‘extensive’ and ‘complete’ for all of those, however in-depth studies carried out for Mymensingh and Dhanbad have been presented here.